Minimax Control for a Class of Linear Systems Subject to Disturbances - Chernousko, F L (Journal of optimization theory and applications, 2005)
A class of linear dynamical control systems subject to uncertain but bounded disturbances is considered. The bounds imposed on the disturbances depend on the control magnitude and grow with the control. This situation occurs if the disturbances are due to the inaccuracy of the control implementation and often takes place in engineering applications such as transportation, aerospace, and robotic systems. Under certain assumptions, the minimax control problem is formulated and solved. Explicit expressions for the optimal control (both open-loop and feedback) are obtained that provide the minimax to the given performance index for arbitrary but bounded disturbances. Examples are given.